Specialized knowledge: Understanding crime analyst’s roles and responsibilities and the impact of their work - Brown, Emma (Criminology & criminal justice, 2024)
Using qualitative interview data, this article examines the role of crime analysts in producing knowledge, as well as the challenges they face. Through the collection and organization of data outlining pertinent information about specific districts, analysts aid in the implementation of policing practices. As such, analysts regard themselves as possessing a specialized form of knowledge, which they incorporate and draw on in the outputs they produce. We conclude that analysts do not always employ rigorous, scientific methodologies, while producing their intelligence outputs, suggesting rather that they rely on their familiarity and specialized knowledge of offenders and crimes in their district. Our findings are important to evaluate and understand how ‘data-driven’ policing is occurring and identifying ways to improve and utilize crime analysis approaches within policing.